Remark on isolated removable singularities of harmonic maps in two dimensions - Changyou Wang (Electronic Journal of Differential Equations)
For a ball $B_R(0)\subset\mathbb{R}^2$, we provide sufficient conditions such that a harmonic map $u\in C^∞(B_R(0)\setminus\{0\}, N)$, with a self-similar bound on its gradient, belong to $C^∞(B_R(0))$. These conditions also guarantee the triviality of such harmonic maps when $R=∞$.